Spatio-Temporal Variation in Growth Performance and Condition of the Winged Pearl Oyster Pteria penguin - Gordon, Sophie E.; Wingfield, Max; Smallhorn-West, Patrick F.; Malimali, Siola’a; Halafihi, Tu’ikologahau; Schoeman, David S.; Southgate, Paul C. (Frontiers in Marine Science, 2021)
Environmental conditions can strongly influence the growth performance of pearl oysters and affect pearl farm production schedules. Growth and condition index of two age cohorts of Pteria penguin were measured for 13 months to investigate differences in growth performance between four culture sites within the northern (Vava’u) and southern (Tongatapu) island groups of the Kingdom of Tonga. Environmental conditions were also measured at culture sites and used to explore potential effects on oyster growth and condition. Between island groups, growth performance of P. penguin was superior at northern sites and was most strongly related to higher water temperatures at these sites. Within the southern island group, growth performance varied significantly between sites and may be driven by differences in wave energy. Monthly growth rates of P. penguin also showed significant temporal variation related to age and environmental conditions. This study demonstrated significant variation in the growth performance of P. penguin at latitudinal and local scales and suggests that in oligotrophic marine environments with minimal terrestrial inputs, such as Tonga, water temperature and wave exposure may be the primary environmental conditions influencing the growth performance of P. penguin. This study therefore recommends that optimal culture sites for P. penguin in Tonga are characterised primarily by warmer water temperatures (25-30 °C) and low wave exposure (<15 joules m2 day-1). Culture of P. penguin at sites with more suitable environmental conditions enables pearl production to begin up to 34.2 % (6.5 months) earlier than at less-suitable sites and this may greatly influence mabé pearl farm profitability and feasibility.